Synthesis and Crystal Structure of 1-Cyclopropyl-6,7-difluoro-8-methoxy-4-oxo- 1,4-dihydro-3-quinoline carboxylic acid-(O3,O4)-bis-(acetate-O)borate - Li, Fei; Zhang, Jie; Jiang, Yu; Jin, Lei; Zhang, Chuan (Asian Journal of Chemistry, 2013)
The crystal structure of the 1-cyclopropyl-6,7-difluoro-8-methoxy-4-oxo-1,4-dihydro-3-quinoline carboxylic acid-(O3,O4)-bis-(acetate-O)borate has been determined by single crystal X-ray diffraction method. The crystal belongs to monoclinic with space group P2(1)/n, with a = 16.818(9), b = 6.585(4), c = 18.663(4)Å, a = 90, b = 107.351(7), g = 90º, V = 1972.8(18)Å3, Z = 4, Dx = 1.479 Mg/m3, l(MoKa) = 0.128, F(000) = 908, μ(MoKa) = 0.128 mm-1, R = 0.1083 and wR = 0.3062 for 2378 reflections with I > 2s(I). The two rings of fluoroquinolone and borate ring are almost coplanar with dihedral angles values lower than 2º. The crystal structure is stabilized by intermolecular hydrogen bonds and p-p stacking interactions.